Discovery Learning Application Using a Rope (Track A Line Idea) to Detect Critical Thinking Skills on Elementary School Students - Trisna Nugraha; Ulfah Samrotul Fuadah; Adila Amalia; Karso Karso (Universitas Pendidikan Indonesia (UPI), 2020)
The study was conducted to collect preliminary data on the effectiveness of the use of Discovery Learning models using TALI (Track A Line Idea) for students' critical thinking skills in mathematics subjects in class VI geometry material in elementary schools. The purpose of this study is to describe whether the application of Discovery Learning models using TALI can be effective against critical thinking skills students on mathematics subjects in class VI geometry material in elementary schools, with research design referring to the syntax of Discovery Learning models that are the benchmarks in learning design namely, (1) providing stimulus; (2) identify the problem; (3) collecting data; (4) data processing; (5) verification; and (6) make conclusions. This study uses a One-shot Case Study experimental research design. With the subjects of class VI students with a total of 17 students. Data collection is done by tests, observations and questionnaires. The results of this study indicate that the motivation and activities of students in Discovery Learning based on TALI are interpreted in high criteria with a percentage range from 84.12% -88.24%. This indicates that Discovery Learning as constructivism learning provides space for students to actively participate in learning by using group learning design and guided discovery so that students keep paying attention to disciplinary aspects in conducting each stage in learning activities. The results of this study indicate that the motivation and activities of students in Discovery Learning based on TALI are interpreted in high criteria with a percentage range from 84.12% -88.24%. This indicates that Discovery Learning as constructivism learning provides space for students to actively participate in learning by using group learning design and guided discovery so that students keep paying attention to disciplinary aspects in conducting each stage in learning activities. The results of this study indicate that the motivation and activities of students in Discovery Learning based on TALI are interpreted in high criteria with a percentage range from 84.12% -88.24%. This indicates that Discovery Learning as constructivism learning provides space for students to actively participate in learning by using group learning design and guided discovery so that students keep paying attention to disciplinary aspects in conducting each stage in learning activities.